2011
DOI: 10.2109/jcersj2.119.93
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical characterization of ceramic tiles prepared by a mixture of Cretaceous and Mio-Pliocene clays from Tunisia: factory and laboratory products

Abstract: Thermal transformations in ceramic products at high temperatures were studied for admixture of Cretaceous and Mio-Pliocene clays, either carbonatic or with plastic behaviour, used for Lab-tiles and factory biscuits with amounts (25%) of quartz-sand added as temper. Clay admixtures contained illites, smectites series, interstratified I/S species and kaolinite. Firing steps of pastes in the factory took place in a tunneled gas kiln at 1080°C; whereas, tiles used for laboratory experiments were fired in an electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The gehlenite as unstable intermediate phases in formed from metakaolinite and calcium oxide recorded in the ClaySej2 sample clays which are rich in calcite when processed at 1000°C (Azzouz et al, 2011). In contrary to El-Mahhlawy (2008) and Manoharan et al (2011), indicating that the presence of anorthite of the fired specimens demonstrated that the firing process reached the equilibrium state; suggesting that the reaction was completed.…”
Section: Study Of the Thermal Behavior By Xrdmentioning
confidence: 92%
See 1 more Smart Citation
“…The gehlenite as unstable intermediate phases in formed from metakaolinite and calcium oxide recorded in the ClaySej2 sample clays which are rich in calcite when processed at 1000°C (Azzouz et al, 2011). In contrary to El-Mahhlawy (2008) and Manoharan et al (2011), indicating that the presence of anorthite of the fired specimens demonstrated that the firing process reached the equilibrium state; suggesting that the reaction was completed.…”
Section: Study Of the Thermal Behavior By Xrdmentioning
confidence: 92%
“…The mineralogical structure and other physico-chemical properties of various types of clay samples have been extensively studied and discussed in the literature (Moore and Reynolds, 1997;Aras, 2004;Azzouz et al, 2011).…”
Section: Study Of the Thermal Behavior By Xrdmentioning
confidence: 99%
“…Above 800°C its mineralogy converts gehlenite, haematite and calcic plagioclase (anorthite) (Figure 9). The anorthite CaAl 2 Si 2 O 8 and gehlenite Ca 2 Al 2 SiO 7 are considered the result of multistage solid-state reactions between the clay matrix and carbonates (González-García et al, 1990; Sedmale et al, 2006; Trindade et al, 2010; Azzouz et al, 2011). Gehlenite starts to form at 1000°C, when manganese is near zero (∼0.01%), by reaction between lime, alumina and silica, the first deriving from carbonates and the latter two from already dehydroxylated phyllosilicates (Trindade et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In Africa, during the last two decades, most study was directed to the characterisation of clay sediments (e.g. Baccour et al, 2008; Mahmoudi et al, 2008; Daoudi et al, 2014; El Ouahabi et al, 2014; Hammami-Ben Zaied et al, 2015; Mahmoudi et al, 2014; Bennour et al 2015a; Mahmoudi et al, 2016), firing transformations of raw materials (Sahnoune et al, 2008; Baccour et al, 2009; Khalfaoui and Hajjaji, 2009; Mahmoudi et al, 2010; Azzouz et al, 2011; Hajjaji and Mezouari, 2011; Bennour et al 2015b; El Ouahabi et al, 2015) and their application in tile and brick products. Despite the antiquity of the pottery industries, few studies have been carried out on the clays and raw materials used in North Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Natural clay minerals contain impurities and are not homogenous, which cause their use to be difficult for technological applications [2]. Therefore, in order to improve their properties, it is necessary to prepare mixtures [7][8][9][10] or to enhance them with the use of additives [11]. Some of the relevant properties for brick masonry have to do with color and brightness [12,13], which ultimately depend on the clay's mineral content and the firing temperature it is subjected to [12].…”
Section: Introductionmentioning
confidence: 99%